Outpatient Care Utilization among Elderly in South Sumatra Based on National Social-Economic Survey Data - Misnaniarti Misnaniarti; Fenny Etrawati (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Implementation of National Health Insurance is thought to be the cause ofincreasing number of visits to health facilities, especially in elderly peoplewho tend to be in sick. This study aims to analyze the outpatient utilizationby elderly in South Sumatera region. Study design was cross-sectional.Samples was elderly in South Sumatra (n = 2,833 people). Study done on2016, using data from Survei Sosial Ekonomi Nasional (Susenas) at 2015. Dataanalysis used chi-square test and multiple logistic regression. Based on thestudy known that outpatient utilization of elderly in all health facilitiesduring the past month amounted to 29.2%. Providers selected when elderlyneeded of outpatient treatment, most often visited to the doctor'spractice/midwife's practice (46.2%), and puskesmas (24.2%). Elderly whohas private health insurance have a tendency was 1.9 times greater (OR=1.9)to utilize outpatient compared to elderly who do not have insurance. Itsconcluded that variables associated with outpatient care utilization are:health insurance membership (OR=1.9) and work activity (OR=1.5). It isrecommended for elderly to remain active in their activities so that they canrealize the healthy and active aging and reduce the sick visits to healthfacilities.